Integrated geophysical investigation of flooding within the campus of Federal College of Education (Technical), Omoku and its environs - Agada Idoko; Johnson C. Ibuot; Moses M.M. Ekpa (EQA)
This study investigates flooding within the campus of the Federal College of Education (Technical), Omoku, and its environs using integrated geophysical methods. Geo-electric resistivity (VES) and Electrical Resistivity Tomography (ERT) were employed to characterize subsurface properties that influence water retention, drainage, and flooding susceptibility. The VES analysis delineated four geo-electric layers with resistivity values ranging from 57.9 to 32,936.7 Ωm, revealing significant subsurface heterogeneity. The topsoil (layer 1) exhibited variable resistivity (86.7–824.4 Ωm), indicating mixed sandy and clayey materials with poor drainage in low-resistivity zones. The second and third layers demonstrated variable thickness and resistivity, reflecting saturated zones prone to water retention and areas with better drainage properties. The fourth layer, likely compact bedrock, exhibited high resistivity, acting as a barrier to water flow and contributing to surface runoff. Secondary geo-electric parameters including reflection coefficients, transverse resistivity, longitudinal resistivity, and anisotropy, provided additional insights. Low resistivity and high anisotropy zones indicated water-saturated or clay-rich materials associated with flood-prone areas. High resistivity and low anisotropy corresponded to better-draining zones with sandy or gravelly materials. ERT profiles complemented the VES results by mapping lateral and vertical variations in resistivity. Low-resistivity zones in the upper subsurface were linked to water-saturated soils, obstructing drainage and increasing flood risk. High-resistivity regions indicated less permeable materials that could exacerbate runoff and surface water accumulation. The study concludes that the interplay of subsurface heterogeneity, saturated zones, and impermeable layers significantly influences flooding in the area. The findings provide critical data for flood risk management and infrastructural planning, highlighting the need for effective drainage systems and soil stabilization measures in vulnerable regions.